Cyclophosphamide, bortezomib and dexamethasone (CyBorD): a promising regimen for renal light chain deposit disease - Dutta, Arunima (BMJ Case Rep, 2020)
Renal light chain deposit disease is a rare disease with rapid progression to renal failure when left untreated. There is no standard treatment available. We present a unique case of renal IgA kappa deposit disease who developed severe decline in renal function within a few months of diagnosis. She was started on a single regimen of cyclophosphamide, bortezomib and dexamethasone (CyBorD) followed by maintenance treatment with bortezomib and dexamethasone leading to rapid improvement of renal function. This is the first case to be reported on renal IgA kappa deposit disease who have responded dramatically to CyBorD without the need for any modification of the regimen or stem cell transplant.